β-carotene attenuates the paradoxical effect of tobacco smoke on the mortality of rats after experimental myocardial infarction - Paiva, Sergio Alberto Rupp de [UNESP]; Novo, Rosangela [UNESP]; Matsubara, Beatriz Bojikian [UNESP]; Matsubara, Luiz Shiguero [UNESP]; Gaiolla, Paula Schmidt Azevedo [UNESP]; Minicucci, Marcos Ferreira [UNESP]; Campana, Álvaro O. [UNESP]; Zornoff, Leonardo Antonio Mamede [UNESP] (My University, 2005)
The objective of this study was to investigate the effects of exposure to tobacco smoke (ETS) in rats that were or were not supplemented with dietary β-carotene (BC), on ventricular remodeling and survival after myocardial infarction (Ml). Rats (n = 189) were allocated to 4 groups: the control group, n = 45; group BC administered 500 mg/kg diet, n = 49, BC supplemented rats; group ETS, n - 55, rats exposed to tobacco smoke; and group BC+ETS, n = 40. Wistar rats weighing 10O g were administered one of the treatments until they weighed 200 to 250 g (∼5 wk). The ETS rats were exposed to cigarette smoke for 30 min 4 times/d, in a chamber connected to a smoking device. After reaching a weight of 200-250 g, rats were subjected to experimental MI (coronary artery occlusion) and mortality rates were determined over the next 105 d. In addition, echocardiographic, isolated heart, morphometrical, and biochemical studies were performed. Mortality data were tested using Kaplan-Meyer curves and other data by 2-way ANOVA. Survival rates were greater in the ETS group (58.2%) than in the control (33.3%) (P = 0.001) and BC+ETS rats (30.0%) (P = 0.007). The groups did not differ in the other comparisons. Left ventricular end-diastolic diameter normalized to body weight was greater and maximal systolic pressures were lower in the ETS groups than in non-ETS groups. Previous exposure to tobacco smoke induced a process of cardiac remodeling after MI. There is a paradoxical protector effect with tobacco smoke exposure, characterized by lower mortality, which is offset by BC supplementation. © 2005 American Society for Nutritional Sciences.
Keywords: β-carotene; Myocardial infarction; Paradoxical effect; Smoking; Ventricular remodeling; beta carotene; cigarette smoke; tobacco smoke; analysis of variance; animal experiment; animal model; animal tissue; body weight; controlled study; disease model; echocardiography; heart infarction; heart left ventricle enddiastolic volume; heart protection; image analysis; isolated heart; Kaplan Meier method; male; morphometrics; mortality; nonhuman; rat; rat strain; smoking; survival rate; systolic blood pressure; Animals; beta Carotene; Diet; Echocardiography; Heart; Male; Myocardial Infarction; Myocardium; Rats; Rats, Wistar; Smoke; Survival Analysis; Tobacco; Ventricular Remodeling; Nicotiana tabacum; Rattus norvegicus